Skyline probabilities with range query on uncertain dimensions - Mohd Saad, Nurul Husna; Ibrahim, Hamidah; Sidi, Fatimah; Yaakob, Razali (Springer, 2019)
To obtain a different perspective,Saad, Nurul Husna Mohd a user often would query information Ibrahim, Hamidah a range of search rather Sidi, Fatimah a fixed search. However, the issue arises when attempting to compute skyline on data that consist of both exact and continuous values. Thus, we propose an algorithm named SkyQUD-T for computing Yaakob, Razali with range query issued on uncertain dimensions by eliminating objects that do not satisfy a given query range before advance processing is performed on the surviving objects. Our behaviour analysis of SkyQUD-T on real and synthetic datasets shows that SkyQUD-T is able to support skyline on data with uncertain dimensions in a given range query